Evaluation of the Protective Role of Pumpkin Seed Oil in Preventing Changes in the Kidney Parenchymal of Rats - Alimova Shakhnoza Azamatovna (Journal of Science in Medicine and Life, 2025)
this article provides information on the results of scientific studies that can assess and study the morphometric indicators of the kidneys of 3-month-old rats who received an energy drink for 90 days and pumpkin seed oil for 30 days.